Estudo de Áreas de Preservação Permanente (APP's) de corpos d'água em zonas urbanas como subsídio à legislação pertinente - Padilha, Daniele Corrêa de Castro (2007)
The purpose of this paper by performing a bibliographic review and case study, in São Carlos (SP), was to study the application of the Code Forest in Permanent Preservation Areas to urban water courses approaching legal aspects and the others laws corresponding. Like this to reach the problems and conflicts in the application of the Code Forest the use and occupation of the soil. Some subsidies were proposed in order to contribute to the definition of new technical and legal references for a more practical and adequate application of the urban APP, according to the context in which it is inserted on the search for a harmonic acquaintance among Man and Nature.